Evaluation of dry bakery waste as replacement of maize in quail diet - GUPTA, ANTRA; KHAN, NAZAM; SHARMA, R K; MAHAJAN, VIKAS; AMRUTKAR, SURAJ (The Indian Journal of Animal Sciences, 2023)
The objective of the study was to compare the effect of replacing maize in quail (Coturnix japonica) diet with bakery waste (BaW) @ 0% (T0), 5% (T1), 10% (T2), 15% (T3) and 20% (T4) on growth, carcass traits, blood and sensory attributes. A day old, 300 commercial straight run quail chicks were randomly allocated to five different treatment groups (n=60 birds/group) for a period of 6 weeks. Eight birds per group were slaughtered at 42 days of age to evaluate carcass and sensory attributes. Result signifies that birds of all groups performed similar in terms of body weight gain, feed conversion and protein efficiency ratio. Also, estimated blood biochemical parameters showed no difference at all replacement levels. Similarly, carcass trait yields, small intestine micrometry and sensory attributes were also statistically similar. It was concluded that maize flakes in quail diet can be safely replaced by BaW up to 20%, without any negative impact.